Pola Asuh Model Gentle Parenting di Era Digital Ekosistem Kecerdasan Artifisial - Azizah Choirunisa Azzahra (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The development of information and communication technology, especially artificial intelligence (AI), has changed the way children interact with the world. The current digital era brings many opportunities, but also challenges, such as mental health risks and difficulties in social development. Therefore, parents need to adopt a relevant parenting approach. This study aims to explore the application of the Gentle Parenting parenting model in a digital context. This study uses the literature review method. This study shows that the application of the Gentle Parenting parenting pattern in the digital era, especially in the artificial intelligence (AI) ecosystem, provides an effective approach for parents in facing increasingly complex technological challenges. With an emphasis on the principles of empathy, open communication, and setting clear boundaries, Gentle Parenting not only helps children use technology wisely but also supports healthy emotional and social development.